Системы охлаждения лопаток современных ГТД - Халатов, А. А.; Борисов, И. И.; Дашевский, Ю. Я. (Eastern-European Journal of Enterprise Technologies, 2009)
The present report gives a brief survey of the turbine first stage nozzle vanes and blades cooling circuits which are often being used in modern advanced gas turbines for power generation. Based on the data from the open literature and own designing experience, advantages and disadvantages of these circuits are considered